Respuesta :
Answer:
The answer to your question is x³ + 11² + 30x
Step-by-step explanation:
Data
x = 0; x = - 5; x = 6
Process
1.- Equal the zeros to zero
x₁ = 0; x₂ + 5 = 0; x₃ + 6 = 0
2.- Multiply the results
x(x + 5)(x + 6) = x [ x² + 6x + 5x + 30]
3.- Simplify
= x [ x² + 11x + 30]
4.- Result
= x³ + 11² + 30x
Answer:
x³ - x²- 30x = 0
Step-by-step explanation:
Given that a polynomial has zeros at x = 0, x = -5 and x = 6.
We convert these into factors by rearrange each equation above to convert the equation into the following form:
{expression} = 0
for x = 0 ( x = 0 is the 1st factor. already in correct form, no further manipulation needed)
for x = -5 (add 5 to both sides)
x + 5 = 0 (x + 5 is the 2nd factor)
for x = 6 (subtract 6 from both sides)
x - 6 = 0 (x - 6 is the 3rd factor)
to obtain the polynomial equation, simply multiply all the factors together and equate to zero, i.e.
(x) · (x+5) · (x-6) = 0
expanding this, we will get
x³ - x²- 30x = 0